Serum Vitamin D levels in Chronic Obstructive Pulmonary Disease - Ajay Kumar; Sanjay Tandon; S T Nagdeote; Kapil Sharma; Akash Shrikhande; Krishna Gopal (International Journal of Medical Research and Review, 2017)
Introduction: Lower serum 25 (0H) Vitamin D is associated with decreased lung function in healthy population and various lung disease. Information on the relationship of levels of serum 25 (OH) Vitamin D with severity of Chronic Obstructive Pulmonary Disease (COPD) is important in standardizing the treatment, in planning appropriate follow up and improving quality of life. This study also warranted further trial to assess the effect of serum 25 (OH) vitamin D on morbidity and mortality in COPD patients.Material and Methods: It was a prospective (observational), cross-sectional study which included all patients with Chronic Obstructive Pulmonary Disease (COPD) attended the Department of Pulmonary Medicine, People’s College of Medical Sciences & RC, Bhopal, over a period of 1 year 6 months.Results: The mean serum 25 (OH) vitamin D level in COPD patients was 27.86±16.47 ng/ml. There was no significant difference in serum 25 (OH) vitamin D between patients in different age groups. The serum 25 (OH) vitamin D levels varied significantly between different GOLD stages and different mMRC dyspnea grades. The patient who had a history of admission for twice or more in the past 1 year had a lower mean serum 25 (OH) vitamin D level as compared to patient with just one or no hospitalization in the past.Conclusion: Decrease serum 25(0H) vitamin D levels were associated with increase airway obstruction.